Continuous biodiesel production based on hand blender technology for sustainable household utilization. (15th May 2021) - Kamjam, Manita; Wongjaikham, Wijittra; Wongsawaeng, Doonyapong; Ngaosuwan, Kanokwan; Kiatkittipong, Worapon; Hosemann, Peter; Assabumrungrat, Suttichai
Abstract: Biodiesel is a widely-used, renewable and environmentally-friendly fuel. The 700 W commercial household hand blender was proposed as simple and effective continuous FAME production technique using a homogeneous catalyst based on fresh reﬁned palm oil, waste cooking oil (WCO), and various vegetable oils as feedstocks. The continuous system was designed and the effects of reaction volume, oil and methanol flow rate, reaction temperature and sodium hydroxide catalyst loading on FAME yield and yield efficiency were explored. The steady-state FAME yield of higher than 96.5% can be achieved from both fresh reﬁned palm oil and WCO with the energy efﬁciency of 18.0 × 10 -4 g/J (fresh reﬁned palm oil) and 19.0 × 10 -4 g/J (WCO) (6:1 methanol to oil molar ratio, reaction volume of 200 mL, total flow rate 12 mL/min, 60 °C, 0.8 wt% sodium hydroxide for palm oil and 1.5 wt% sodium hydroxide for WCO, highest stirring speed (10, 640 rpm) at 220 V, no insulation), indicating that WCO shows good potential as a feedstock of biodiesel production. All properties of the synthesized FAMEs satisfy the EN 14214 and ASTM D 6751 standards. FAME produced from palm oil showed the highest FAME content, followed by sunflower oil and corn oil. The simple and low-cost kitchen hand blender is an alternative process intensification device to efficiently produce good quality FAME for household users, which is a convenient and environmentally-friendly method. WCO can also be recycled to produce a product with high economic value. Graphical abstract: Image 1 Highlights: Successful continuous FAME production using 700 W household hand blender. Low residence time of 16.7 min can produce biodiesel of 0.6 kg/h. This process intensification required low energy consumption. Outstanding energy efﬁciency of 18.0 × 10 −4 g/J for fresh palm oil. Produced biodiesel complied with EN 14214 and ASTM D 6751 standards.